Investigation of biomass, RDF and coal ash-related problems: Impact on metallic heat exchanger surfaces of boilers. (15th October 2022) - Kaniowski, Wiesław; Taler, Jan; Wang, Xuebin; Kalemba-Rec, Izabela; Gajek, Marcin; Mlonka-Mędrala, Agata; Nowak-Woźny, Dorota; Magdziarz, Aneta
Highlights: Four different ash depositions were investigated. Transformation of ashes was studied experimentally and by FactSage. RDF and biomass ashes were rich in Cl and K. Long-term corrosion tests were carried out. Nickel-coating limited ash influence on steel surface. Abstract: The goal of this work was to study the corrosion resistance of boiler steel and protective alloy coatings. Four ashes obtained from wood biomass, straw, refused-derived fuel and coal were analysed. The aggressive components of ash, such as potassium, sodium, sulphur and chlorine, can accelerate the operating problems of heat exchanging surfaces in power boilers, leading to enhanced slagging, fouling, agglomeration of ash, and corrosion. Four boiler steels were chosen for detailed investigation: 16Mo3, P265GH, Inconel 625 and 686. They were covered with ashes, placed in a furnace and heated through 4 months at 750 °C under oxidizing conditions. Multifaceted ash analysis (chemical composition, thermal behaviour, phase composition, and characteristic melting temperatures) was performed. Additionally, both slagging and fouling indices were calculated to predict the sintering properties of the studied ashes. The surfaces of studied steels after the exposure of ash presence were analysed using SEM-EDS technique. The results showed that the corrosive impact of the ashes depended on the aggressive components present in the ash. Furthermore, FactSage thermochemical equilibrium calculations were used to predict the amount of liquid slag and solid phases under the studied conditions and to determine the transformation of the mineral phases of the ash.